First record of the Nearctic Zelus renardii (Heteroptera, Reduviidae, Harpactocorinae) in Europe - Petrakis, P. V.; Moulet, P. (ENTOMOLOGIA HELLENICA, 2011)
The Nearctic assasin bug species Zelus reinardii was found for the first time in Attica, Greece, Europe. This species is a generalist predator which can contribute to the control of insect pests. This is also a known predator of several biological control agents of pests. Therefore, its naturalization in Greece is potentially problematic in economic settings since the insect may act as both an intraguild and a beneficial predator. The risky nature of importation in other areas (e.g. Hawaii) showed the possibility of these ecological roles.